Ketoprofen-Tromethamine: Binary Phase Diagram of Multicomponent Crystal, Dissolution Rate, and Analgesic Activity Evaluation - Hasanah, Uswatul; Badriyya, Elsa; Safitri, Reza; Yuliza, Sukma; Ihsan, Ikhwanul; Saafrida; Rosaini, Henni; Jessica, Adhitya; Zaini, Erizal (Science and Technology Indonesia, 2024)
Ketoprofen is a non-steroidal anti-inflammatory drug (NSAID) whose formulation options are limited due to its low dissolution rate in aqueous media. This research aimed to enhance the solubility of ketoprofen in distilled water and to compare the anti-inflammatory and analgesic effects of its resulting multicomponent crystal with tromethamine. The binary phase diagram of ketoprofen-tromethamine was created across molar ratios ranging from 1:9 to 9:1. The multicomponent crystal comprising ketoprofen and tromethamine in the selected ratio was synthesized using a solvent drop grinding method and subjected to further characterization for thermal properties, crystallinity, chemical groups, and morphology. The dissolution rate assessments were evaluated in CO2-free distilled water. Pharmacological analyses examined the anti-inflammatory and analgesic effects of the multicomponent crystal. The binary phase analysis identified the 5:5 (1:1) molar ratio as optimal in forming a multicomponent crystal. Thermograms and diffractograms revealed crystalline alterations attributed to a new crystalline phase. The new multicomponent crystal exhibited approximately 2.7 times higher dissolution rate after 30 minutes, outperforming pure ketoprofen. Pharmacological assessments demonstrated superior analgesic effects of the multicomponent crystal. In summary, the ketoprofen-tromethamine cocrystal in 1:1 molar ratio offers enhanced dissolution rate and provides better analgesic activity than ketoprofen alone.